2006
DOI: 10.1111/j.1365-2044.2006.04552.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia after cardiac arrest: a survey of practice in intensive care units in the United Kingdom

Abstract: Summary A telephone survey was carried out on the use of hypothermia as part of the management of unconscious patients following cardiac arrest admitted to United Kingdom (UK) intensive care units (ICUs). All 256 UK ICUs listed in the Critical Care Services Manual 2004 were contacted to determine how many units have implemented therapeutic hypothermia for unconscious patients admitted following cardiac arrest, how it is implemented, and the reasons for non‐implementation. Two hundred and forty‐six (98.4%) ICUs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 19 publications
7
67
0
2
Order By: Relevance
“…A survey of all ICUs in the United Kingdom showed that by 2006, only 27% of units had ever used mild hypothermia to treat post-cardiac arrest patients. 365 Similar findings were reported in surveys in the United States 366,367 and Germany. 368 Successful implementation has been described by several centers, however.…”
Section: Existing Studies Showing Poor Implementationsupporting
confidence: 76%
“…A survey of all ICUs in the United Kingdom showed that by 2006, only 27% of units had ever used mild hypothermia to treat post-cardiac arrest patients. 365 Similar findings were reported in surveys in the United States 366,367 and Germany. 368 Successful implementation has been described by several centers, however.…”
Section: Existing Studies Showing Poor Implementationsupporting
confidence: 76%
“…We were unable to discriminate those patients with deliberately induced hypothermia from those with unintentional hypothermia, making it difficult to interpret these data. However, a recent telephone survey of UK practice indicates that very few of these patients would have been treated with induced hypothermia [38].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic hypothermia has been shown to improve neurological outcome after cardiac arrest in two randomised clinical trials [9,10]. Consequently, reducing body temperature to 32 -34°C with subsequent rewarming after 24-48 h has become a standard procedure following cardiac arrest [1,3,[11][12][13]. Therefore, haemodynamic and pulmonary variables need to be evaluated in these patients under both normothermic and hypothermic conditions.…”
mentioning
confidence: 99%